Assessment of the Relationship Between Depression and Bone Mineral Density and Quality of Life in Patients with Postmenopausal Osteoporosis - Halil Koyuncu; İlknur Aktaş; Ahmet Dinç; İmdat Özkul; Teoman Aydın; Erdal Yücel; Ömer Kocaman; Halime Toros (Galenos Yayinevi, 2003)
The aim of this study was to determined the effects of depression on bone loss and quality of life in postmenopausal osteoporotic (PMO) women. Seventy two females (mean age 65 ± 6.9) were included in this study. Out of these patients, 27 (37.5%) had depression, 45 (62.5%) were normal. All cases were evaluated by DXA, Hamilton depression scale, Short Form-36 (SF-36) scale and visual analog scale. In the patients with depression, L1-L4 t-score (-3.29 ± 1.07), femur neck t-score (-2.60 ± 1.00) and z-score (-0.97 ± 0.82) were significantly lower than PMO patients without depression (respectively; -2.71 ± 0.83, -1.86 ± 1.16 and -0.50 ± 0.91). SF-36 scores (75.9 ± 19.8) were lower in patients with depression than patients without depression (86.5 ± 14.4) (p=0.041). Negative correlations between Hamilton score and L1-L4 z-score (R=-0.432, p=0.024), femur neck t-score (R=-0.528, p=0.005) were found. In conclusion, postmenopausal bone loss was higher and functional capasity was lower in patients with depression.